2015
DOI: 10.3828/tpr.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Matching the process to the challenge within small town regeneration

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported License Newcastle University ePrints-eprint.ncl.ac.uk Powe NA, Pringle R, Hart T. Matching the process to the challenge within small town regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Often, they offer fewer amenities or other benefits of agglomeration than larger cities (Lewis & Stillman, ; Maré, ). We also observed that in contradiction to these somewhat depressing prognostications, the international literature suggests that adequately supported locally initiated regeneration efforts can create positive change in regional towns and their rural hinterlands (Powe, Pringle, & Hart, ; Spires & Moore, ). Influenced by this work our research was designed to examine regeneration activities in a sample of regional towns and to add a stronger New Zealand perspective to the small‐town regeneration literature.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Often, they offer fewer amenities or other benefits of agglomeration than larger cities (Lewis & Stillman, ; Maré, ). We also observed that in contradiction to these somewhat depressing prognostications, the international literature suggests that adequately supported locally initiated regeneration efforts can create positive change in regional towns and their rural hinterlands (Powe, Pringle, & Hart, ; Spires & Moore, ). Influenced by this work our research was designed to examine regeneration activities in a sample of regional towns and to add a stronger New Zealand perspective to the small‐town regeneration literature.…”
Section: Introductionmentioning
confidence: 64%
“…Having much the same foci, regeneration policies and initiatives have also been developed to advance the renewal and development of small regional towns and associated rural areas. As do Roberts et al () in the urban context, Powe et al () suggest in their review of two decades of international literature on small‐town regeneration that the field is challenging and complex. One of the main distinguishing factors between work in larger urban centres, and efforts in small‐town and rural regeneration, is that in the latter, local funding levels are often not sufficient to the task and skilled practitioners are in short supply.…”
Section: Understanding and Studying Regional And Small‐town Regeneratmentioning
confidence: 98%
See 2 more Smart Citations
“…(interview with author, 4 April 2013).Incredible Edible Todmorden, YorkshireTodmorden is a small town on the Yorkshire/Lancashire border that experienced a long decline after the demise of the textile industry in the late 20th century. It has been the subject of numerous 'regeneration' initiatives, with limited evidence of impact(Powe, Pringle and Hart 2015). A turning point for Todmorden was the emergence of the Incredible Edible movement, which encourages local people to grow and share fruit and vegetables.…”
mentioning
confidence: 99%